Inheritance of aposporous apomixis in interspecific hybrids derived from sexual paspalum plicatulum and apomictic paspalum guenoarum - Aguilera, Patricia Mabel (2015)
Fil: Aguilera, Patricia Mabel. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.